Decoding Ancient Egyptian Metalworking: A Textual Analysis of Old Kingdom Iconography (Enki & Ptah. Journal of Technology and Trade in Ancient Egypt and Western Asia, 2025)
The study of ancient Egyptian metallurgy is an emerging field. While hundreds of analyses of the chemical composition and technology of metal objects have been conducted, there is incomplete knowledge about the techniques, manufacturing processes, and working conditions of the early metalworkers in the region. The metalworking scenes in ancient Egypt, are, on one hand, informative, since they depict several stages of metalworking, from the weighing of crude metal to the production of metal sheets for the fabrication of vessels. On the other hand, the accompanying texts delve into critical aspects of the depicted activities, offering valuable insights into technical details. This paper examines the texts accompanying the metalworking scenes from the Old Kingdom to offer a clearer understanding of the various stages in the metalworking process, the technical treatment involved, and the working conditions in one of the most demanding industries of ancient Egypt. It will also cross-reference visual depictions with existing textual sources to assess the accuracy and depth of knowledge regarding metalworking practices.